The role TV plays in 21st century lives - Oldham, Marie (Henry Stewart Talks, 2009)
Needstates, Role of TV, Sociability, connectivity and potency, TV that unites, Convenience, potency and connectivity, How people are watching TV now, Implications for advertisers
Archived at 2022/04/07